2019
DOI: 10.1001/jamacardio.2019.3502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1 or 2 Doses of Inclisiran on Low-Density Lipoprotein Cholesterol Levels

Abstract: IMPORTANCE Sustained reductions in low-density lipoprotein cholesterol (LDL-C) with lipid-lowering therapies that require frequent dosing are reliant on patient adherence, and poor adherence is associated with worse clinical outcomes.OBJECTIVE To determine whether inclisiran, a small interfering RNA, reduces mean LDL-C exposure with an infrequent dosing regimen. DESIGN, SETTING, AND PARTICIPANTS Prespecified analysis of a randomized, double-blind, placebo-controlled multicenter phase 2 clinical trial. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 16 publications
(34 reference statements)
3
63
0
3
Order By: Relevance
“…3 Data from the same trial following the same patients over a period of 360 days suggested that inclisiran might provide sustained reductions in LDL cholesterol levels, with the potential for a dosing schedule of once every 6 months. 4…”
mentioning
confidence: 99%
“…3 Data from the same trial following the same patients over a period of 360 days suggested that inclisiran might provide sustained reductions in LDL cholesterol levels, with the potential for a dosing schedule of once every 6 months. 4…”
mentioning
confidence: 99%
“…In addition, these results may be explained by the enhanced permeability and retention effect that is more prominent in early, developing atherosclerosis compared to late-stage plaques (35). Interestingly, inclisiran, an investigational siRNA-based therapy in clinical trials as a PCSK9 inhibitor for atherosclerosis, has also shown a single dose to have long-term benefits in humans for up to a year (36). Overall, our results demonstrate miR-145 therapy as a viable and safe strategy for treating atherosclerosis, and the benefit of infrequent dosing may be used to supplement patients who are intolerant of current firstline, atherosclerosis therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies consistently demonstrated the effectiveness of inclisiran in reducing the plasma proprotein convertase subtilisin kexin type 9 and LDL cholesterol levels in healthy individuals and patients at high risk for cardiovascular disease who had elevated LDL cholesterol levels ( Fitzgerald et al, 2014 , 2017 ; Ray et al, 2017 ). Moreover, a single-dose treatment with inclisiran was shown to cause a durable reduction in LDL cholesterol levels among the subjects over 1 year ( Ray et al, 2019 ), and inclisiran showed similar efficacy and safety profiles among individuals with normal and impaired renal functions ( Wright et al, 2020 ). A double-blind, placebo-controlled, and open-label phase II/III study (NCT03851705) is ongoing to evaluate the safety and efficacy of inclisiran in patients with HoFH.…”
Section: Rnas As Therapeutic Drugsmentioning
confidence: 99%